Automatic determination of the mitotic index with digital image processing methods. - Garza, María (Revista Mexicana de Ingenieria Biomedica, 1991)
A system is proposed to identify and count lymphocyte and lymphocyte nuclei in the process of cell division (mitosis) to later calculate the mitotic index. The images are obtained from an optical microscope with a lateral amplification of 20X x 3.3X (66X). they are digitized in a space of 512 x 480x 8 bits. Initially they are processed with a low frequency noise filter and segmentation. Segmentation produces a series of objects that are classified according to certain criteria established in a previous training, to then make a decision about their nature.